Perancangan Sistem Informasi Penjualan Sepeda Motor pada PT. XYZ (Journal Innovations Computer Science, 2022)
The research aims at developing an online-based system with a focus that the feature also has an API (Application Programming Interface) service that can spread products on various e-commerce in Indonesia. In the process of developing software or motorcycle sales system applications, researchers use the Spiral method. The programming language used is PHP with MySQL as the database and uses the Vue.js framework. From the results of research and observations that have been made at PT. XYZ, it can be concluded that; From the results of the manufacture of motorcycle sales information system PT. XYZ web-based parties make it easy to inform PT. XYZ which is ready to be sold through the sales system. With the sales website, buyers can access and get information and motorcycle sales of PT. XYZ quickly from his home, and can choose the desired motorcycle to be purchased, and the motorcycle sales application at PT. XYZ can handle and control and supervise motorcycle sales transaction data, create sales invoices that can avoid delays and in making sales reports for each transaction activity, use APIs by disseminating using the Bukalapak and Tokopedia APIs and successfully synchronizing but still need testing and development that focuses on products on the Android platform.